Evaluación de los medios de almacenamiento de la información contable en la Universidad del Quindío en su sede se Armenia (2015)
The main objective of this work is to evaluate the means of storing accounting information at the University of Quindío, identifying the type of this information, the media where it is stored and the storage process, in addition to determining the means with which they are optimal and that consistently meets the needs will increase as the university expands. The evaluation was performed in air directly related to the storage of accounting information, which is the area of accounting where all information from both treasury, budgeting, portfolio, tuition and humane management forming the fiscal, financial and administrative information crosses University of Quindío, and Systems area, which is responsible for all information system processes and infrastructure of the university are working properly. To collect the information different research techniques but the main and most useful used was the interview yielded information processes directly from the officer, but for safety reasons much of the information is restricted, is achieving collect necessary to analyze the risks and determine the means to be more useful and efficient for the storage of accounting information is safe and effective, but could also be identified that storage depends not only on the media or the hardware, but the software to process information it is safeguarded, the network on which the software runs and the energy that allows the network to work, so all these elements had to be also under review for giving lessons which can help prevent threats that currently have the storage media.